URBAN MUSIC OF ALEXANDRAPOLE AND KOMITAS - Harutyunyan H. H. (International Journal of Innovative Technologies in Social Science, 2021)
The ašugh society in Alexandrapol (now Gyumri) emerged and developed under the immediate effect of historical-cultural processes. This society carried out an important mission with the public acknowledgment it possessed. It was an embodiment of the new qualities in the Armenian national thought in all the spheres of the ašugh school: ideological, propagandistic, music-poetic, etc.Among the songs leaning towards the Near East ašugh traditions that constituted the huge heritage of about forty ašułs, the songs based on Armenian verses display the modal, prosodic and stylistic features of Armenian monodic music. My paper presents the criteria in the song-creation of the ašugh society of Alexandrapol, which are fully in line with Komitas’s fundamental principles of Armenian national song art.